Development of a novel mobile robotic system for large-scale manufacturing. (December 2021) - Ding, Yabin; Zhang, Zeyang; Liu, Xianping; Fu, Jinsheng; Huang, Tian
The high demand of efficient large-scale machining operations by concurrently decreasing operating time and costs has led to an increasing usage of mobile robotic systems. This paper introduces a mobile robotic system which is consisted of a hybrid robot named TriMule on an automated guided vehicle, and a fringe-projection-based measurement system. TriMule exhibits desirable performance in terms of rigidity, accuracy, work envelop and reconfigurability. It is therefore suitable to be built on an autonomous platform for multi-station manufacturing in situ. In order to increase the absolute accuracy of the mobile robotic system, the fringe-projection-based measurement system obtains high accuracy and high density cloud to measure the position and orientation of the robot and workpiece in relation to each other. This system is suitable for large-scale manufacturing in situ, drilling, riveting and high-speed milling for example.